Autogenous dentin for socket preservation: a narrative review of clinical outcomes compared to spontaneous healing - Jalůvka, Petr; Šrubař, Jan; Starosta, Martin (Frontiers in Dental Medicine, 2025)
Socket preservation after tooth extraction is a critical procedure to maintain alveolar ridge dimensions for future prosthetic rehabilitation. Autogenous dentin has emerged as a promising graft material due to its biocompatibility, osteoconductivity, and similarity in composition to bone. A systematic search of MEDLINE (PubMed), Scopus, and Web of Science was conducted in January 2025 using a defined MeSH-based strategy. The search was limited to human clinical studies published in the past ten years. Only studies directly comparing groups with autogenous dentin grafts and spontaneous healing without augmentation were included. Six studies met the criteria and were included in the final review, all confirming the safety and biocompatibility of autogenous dentin. Histological evaluations showed active bone formation around dentin particles and high osteoblastic activity without inflammatory response. Cone beam Computed Tomography (CBCT) analysis, performed in most studies, revealed significantly better preservation of ridge dimensions in autogenous dentin matrix (ADM)-augmented sites, especially in the coronal third of the socket. One study highlighted successful outcomes even in periodontally compromised molar extractions. Despite the general agreement among studies, further research (ideally with standardized protocols) is needed to confirm long-term efficacy in diverse clinical scenarios.